2018
DOI: 10.1159/000488207
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Surfactants and Fluoride against Enamel Erosion

Abstract: This study investigated the effect of surfactants associated with sodium fluoride (NaF) on enamel erosion prevention, using an erosion-remineralization in vitro model. Sodium lauryl sulfate (SLS), polysorbate 20 (P20), and cocoamidopropyl betaine (CAPB) were tested, at concentrations of 1.0 and 1.5%, and associated or not with NaF (275 ppm). The control groups were distilled water and the NaF solution. Bovine enamel samples (n = 12) were prepared and submitted to a 5-day cycling model: acid challenge (0.3% cit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 38 publications
0
7
0
1
Order By: Relevance
“…We expected that both S-F and T-F would be present after the application of fluoride-containing dental materials. Many studies have reported on S-F following fluoride application [ 8 , 9 , 10 ]. However, we focused on T-F, which could be detected by using an in-air micro-PIXE/PIGE system.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We expected that both S-F and T-F would be present after the application of fluoride-containing dental materials. Many studies have reported on S-F following fluoride application [ 8 , 9 , 10 ]. However, we focused on T-F, which could be detected by using an in-air micro-PIXE/PIGE system.…”
Section: Discussionmentioning
confidence: 99%
“…Fluoride and calcium concentrations were measured in two adjacent slices. One slice was immersed in 50 mL of 1M KOH solution for 24 h and then rinsed with water for 5 min to remove S-F according to previous studies [ 8 , 10 ] and analyze the T-F. The other slice was not subjected to KOH treatment and was used for W–F analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Human saliva was used as the remineralization solution and for acquired pellicle formation. It was collected from 15 donors who had no general and oral diseases, were not pregnant, and had a stimulated salivary flow higher than 0.8 mL/min and an unstimulated flow higher than 0.2 mL/min) [Zanatta et al, 2019]. Before the saliva collection, the donors were instructed to brush their teeth with a fluoride-free dentifrice (Cocoricó, Bitufo, São Paulo, Brazil).…”
Section: Erosive Challenge and Remineralizationmentioning
confidence: 99%
“…Além disso, o mecanismo de ação do Clinpro não é o mesmo do que o de uma pasta profilática. O selante ionomérico tem uma maior adesão aos substratos dentais, com resultados clínicos positivos na redução da dor causada pela HD(106), o que nos levou a escolhê-lo como controle positivo.…”
unclassified